Cronicles - Ibe, Adimchinma (Goodbooks Africa, 2012)
Cronicles is a novel that shows corruption, politics, and murder being the same worldwide. The hero Tammy Peterside, a flawed character who is well aware of his own shortcomings, but who nonetheless is one of the few honourable people in the city. Despite his flaws, Tammy has caught the police chief's eye, and so he is assigned to investigate the shooting of Edward Okeke, an accountant with the Oil Producing States Development Service...
Keywords: Juvenile Fiction